2010
DOI: 10.1038/ajh.2010.28
|View full text |Cite
|
Sign up to set email alerts
|

Race/Ethnicity and Hypertension: The Role of Social Support

Abstract: BACKGROUND Social support is an important determinant of health, yet understanding of its contribution to racial disparities in hypertension is limited. Many studies have focused on the relationship between hypertension and social support, or race/ethnicity and social support, but few have examined the inter-relationship between race/ethnicity, social support, and hypertension. The objective of this study was to determine whether the relationship between race/ethnicity and hypertension varied by level of socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(72 citation statements)
references
References 36 publications
(57 reference statements)
4
66
1
1
Order By: Relevance
“…Despite the predisposing factors in hypertension such as education, BMI, physical activities observed largely among Hispanic ethnicity, hypertension prevalence was lowest among Hispanics. e observed lowest prevalence in HTN may be explained by the "Hispanic Paradox" which claims the role of family support system in buffering stress, thus decreasing blood pressure through arterial relaxation and the reduction in the catecholamine synthesis (norepinephrine, dopamine, and epinephrine) [28]. e results from this study is indicative of the persistent racial/ethnic disparities in hypertension prevalence and the factors that predispose to hypertension.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Despite the predisposing factors in hypertension such as education, BMI, physical activities observed largely among Hispanic ethnicity, hypertension prevalence was lowest among Hispanics. e observed lowest prevalence in HTN may be explained by the "Hispanic Paradox" which claims the role of family support system in buffering stress, thus decreasing blood pressure through arterial relaxation and the reduction in the catecholamine synthesis (norepinephrine, dopamine, and epinephrine) [28]. e results from this study is indicative of the persistent racial/ethnic disparities in hypertension prevalence and the factors that predispose to hypertension.…”
Section: Discussionmentioning
confidence: 55%
“…e etiology of hypertension is multifactorial and incidence, prevalence and mortality vary by race/ethnicity [5][6][7]. A study has shown that the age-adjusted prevalence of hypertension by race, in the year [2003][2004], among the United States residents of age 20 years or older was 39.1% non-Hispanic Black, 28.5% non-Hispanic White, and 27.8% Hispanic, while age-unadjusted prevalence rate was 34.4%, 30.3%, and 16.9% for three racial groups, respectively [8]. However, it is not fully understood whether the observed variance is due to race or other factors associated with race or hypertensive risk factors per se.…”
Section: Introductionmentioning
confidence: 99%
“…That is, living in postcode sectors with lower levels of lack of fairness may enhance the likelihood of accessing various forms of support, which protects against stressful events. 11 As recently emphasized, 12 there may be beneficial effects of social support on hypertension. Therefore, further studies are needed to clarify more comprehensive understanding of the effects of social capital and social support on blood pressure.…”
Section: Discussionmentioning
confidence: 98%
“…Social support and integration have been linked to hypertension rates (see review by Uchino et al 1996;Bell et al 2010), although studies suggest that aspects of both influence hypertension through psychological well-being (Bosworth et al 2003;Gorman and Sivaganesan 2007).…”
Section: Potential Mechanismsmentioning
confidence: 98%